(untitled) (Práxis Educativa, 2018)
The current university education cannot remain separate from what happens in society. Consequently, the relationship between teaching content and social demands must be strengthened. We intend to introduce social justice in university teaching through the use of social texts in the teaching-learning process. These texts are related specifically to cultural differences, the reality of people in countries of the South and that of women in different countries. The use of multimodal texts in teaching is encouraged so that students learn to read texts in which images appear. For this reason, a proposal of activities carried out by university students of English Studies is made in order to deepen social justice, openness to other cultures and the acquisition of competences. This educational proposal is part of the critical pedagogy of Paulo Freire. Keywords: Social justice. Paulo Freire. University education.